Resiliensi sebagai Prediktor Teacher Well-Being - Sekar Aulia Winesa; Airin Yustikarini Saleh (Fakultas Psikologi Universitas Pancasila, 2020)
Heavy workload could make teachers have negative perceptions about teacher well-being. Therefore teachers need resilience to withstand the heavy workloads to maintain their well-being. Based on the background, the purpose of this study is to find a relationship between resilience and teacher well-being. It is assumed that resilience can be a predictor of teacher well-being. Participants are 263 teachers who actively teach at various levels of school with teaching duration ranging from 6 months to above 30 years. Data analysis performed using Pearson correlation analysis to see the relationship between variables and simple linear regression to see the role of resilience to teacher well-being. The results showed that resilience has a significant relationship with teacher well-being (value r = .333, p <.01). It means that if the resilience value increases, the value of teacher well-being increases. The results of linear regression analysis showed that resilience explained 11.1% of the teacher well-being variance. This study provides awareness that resilience to teachers can be one of the important things to consider to improve teacher well-being. Based on the results obtained, researchers hope the world of education can provide interventions related to resilience to improve teacher well-being.